(3NdGUI GdPgH GdjhSaj (B((3OjhGf TYQ(B)s - (3LeGd GdOjf jhSa Hf RcQjG GdeZQHj,J (B1019 (3g` s
(3ChdgG (B:s
(3hHYO(B: (3bGd GdabjQ jhSa GdeZQHj(B: (3hJMbbJ Cf GdTYQGA edhc GdcdGe hGdHjGf, hCfg dGHO dcd edc ef OjhGf, LeYJ NdGUI ef Pdc GdPgH GbJOGA aj Pdc HCgd GdCOH s
(3BNQgG (B:s
(3hbGd YaG Gddg Yfg ef GdTYQ hgh NJGe gPG GdOjhGf(B: (3jGQHfG aGdWa HfG jRhd YfG cd VjQ hGZaQ dfG eG bO eVi jGQHfG hGNJe HNjQ s
(3Vef eLehY , JQJjHgG (B: (3ef U (B109 - (3U(B251s
(3GfXQg eY ePgHGJ GdMRf aj GdeGA hGdNVQI hGdhLg GdMSf dg JMJ Qbe (B2261 (3COHs
(3ocJHJ aj MjGI GdeDdas
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B231 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B301 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B2 - (3U (B566s
Keywords: (3GdCOHs